REVIEWING THE INTERPRETATION OF 'ILMI ON THE COSMOLOGICAL VERSES OF THE QUR'AN IN CONTEMPORARY DISCOURSE - Cahyono, Agung Mandiro; Bahrudin, Moh.; Mukti, Anwar; Fathoni, Ahmad Nur; Hakim, M. Luqman; Evannathan, M. Farrel (West Science Islamic Studies, 2023)
The integration of science in the interpretation of the Qur'an (tafsir 'ilmi), especially in cosmological verses, has become an important phenomenon in contemporary Islamic studies. This literature review aims to map the development, examine methods, and identify epistemological and methodological challenges in the approach. The research uses a literature study method with thematic content analysis, sourced from classical interpretation, scientific-modern interpretation, and academic studies on the epistemology of interpretation and cosmology. The results of the study show that the integration of science is carried out through various patterns, such as technical correspondence, apologetic confirmation, and conceptual harmonization. Cosmological verses such as QS. Al-Anbiya' 30, QS. Adz-Dzariyat 47, and QS. Yasin 38–40 was the main focus. However, this approach has been criticized for the risk of imposing meaning, reducing the theological message, and relying on tentative scientific theories. The epistemological challenge of bringing together transcendent and normative revelation with immanent and descriptive science is also a crucial issue. This study confirms that the sustainability of tafsir 'ilmi requires a rigorous methodology by placing the linguistic authority and context of the Qur'an as the main foundation. It is recommended that there be clearer methodological guidelines, multidisciplinary collaboration, and further research on the theme of cosmology with a philosophical-hermeneutical approach. The integration of science should ultimately lead to the deepening of faith and obedience, not merely scientific proof.